Ab initio calculations of spin-nonconserving exciton–phonon scattering in monolayer transition metal dichalcogenides. (29th June 2022) - Zhang, Xiao-Wei; Cao, Ting
Abstract: We investigate the spin-nonconserving relaxation channel of excitons by their couplings with phonons in two-dimensional transition metal dichalcogenides using ab initio approaches. Combining GW-Bethe–Salpeter equation method and density functional perturbation theory, we calculate the electron–phonon and exciton–phonon coupling matrix elements for the spin-flip scattering in monolayer WSe2, and further analyze the microscopic mechanisms influencing these scattering strengths. We find that phonons could produce effective in-plane magnetic fields which flip spin of excitons, giving rise to relaxation channels complimentary to the spin-conserving relaxation. Finally, we calculate temperature-dependent spin-flip exciton–phonon relaxation times. Our method and analysis can be generalized to study other two-dimensional materials and would stimulate experimental measurements of spin-flip exciton relaxation dynamics.